Pessoas com deficiência no mercado de trabalho e a lógica utilitarista do capital - Torres, Natali Esteve (2023)
Understanding labor relations as structurants of the ways of life and society being organized by class struggle, it was aimed to understand how the access process to the labor market of people with disabilities, former students of higher education courses and its unfoldings are characterized. In order to answer the main question raised, we sought to identify the access routes to the labor market for this group, to analyze the barriers regarding labor market entry and, at last, to get to know and understand the challenges faced by people with disabilities in their labor activities. First, the construction of the theoretical framework was carried out, subdivided into three stages. The first one, approaching the conceptions of labor from a Marxist perspective. The second chapter presents the conceptions related to education and the public policies on education aimed at people with disabilities and, finally, in the third part, it was sought to carry out a survey on the history of people with disabilities in addition to presenting the current data of this group in Brazil. Then, the state of knowledge was conducted with the purpose of checking what has been produced in the area through a search in the theses and dissertations library, in which 14 papers were analyzed. A research supported by dialectical historical materialism was developed as methodology, in which people with disabilities, graduated in different courses and institutions of higher education, were interviewed. Altogether, 14 interviews were used throughout the research. The data analysis took place through the creation of nuclei of meaning, an analysis methodology, which as well as the conceptions about disability present in the text, are based on the Cultural-historical Theory. Four major themes were addressed: accessibility and ableism in the graduation course; disability in the labor market and the utilitarian logic of capital; precarization and illness in the labor market and, finally, the logic that imposes the blaming and individualization of illness, building up secondary disability. It was also pointed out that as a result of the major themes worked on, there is an increase in the process of illness and impoverishment of this group.